Youth entrepreneur development project VSO ICS entrepreneur : North-West cycle 2 - Ferdous, Farhan (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.